Assessing Socio-Economic Productivities of Staple Crops: An Evidence from Oransbari Settlement Unit, West Papua - Sagrim, Meky (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Agricultural crops are vital for local food security and rural livelihoods but face challenges such as limited access to modern agricultural inputs, soil fertility issues, and climate variability. The study objective is to assess the productivity of staple crops—rice, corn, and soybean—in Oransbari Settlement Unit, South Manokwari, West Papua. Using a mixed-methods approach, this research combines farmer surveys and official document analysis to evaluate productivity levels, economic benefit, and identify factors influencing yields. The findings reveal that farmers consider agriculture as their primary livelihood (100% for paddy, 87% for corn, 75% for soybeans). Paddy farming is traditional and labour-intensive, corn and beans are emerging as modern, flexible alternatives. Paddy farmers are active in agribusiness (100%), while corn (87%) and soybeans (75%) show some inactive participants. Most farmers have 0-10 years of experience in corn (73%) and soybeans (75%), while paddy farmers are more experienced (47% with 11-20 years, and 15% with 21-30 years). Productivity of paddy is 4.19 tons/ha while on-site productivity shown 5.87 tons/ha, corn is 5 tons/ha, and soybeans productivity is 2.43 tons/ha. Net Income of paddy is IDR 34,322,343, corn is IDR 56,019,996, and soybeans is IDR 40,282,925. Corn generates the highest income. Sustainability, inclusivity, and productivity in the farming sector dan be supported by tailored interventions. Targeted interventions to address costs, land use, and productivity gaps could improve overall sustainability and profitability across all crops.